2003
DOI: 10.1128/jcm.41.12.5419-5428.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Parameters for Precise Diagnosis of Asymptomatic Epstein-Barr Virus Reactivation in Healthy Carriers

Abstract: Asymptomatic Epstein-Barr virus (EBV) reactivations periodically occur in oral mucosa-associated lymphoid tissues. Until now, EBV reactivation has been diagnosed by serologic profiles that suggest virus replication. Serologic responses, however, are delayed and do not necessarily indicate ongoing replicative activity. The aim of the present study was to establish in healthy carriers parameters for a molecular diagnosis of reactivated EBV infection. Recent studies emphasized the association of an increase in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
2
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 35 publications
3
84
2
8
Order By: Relevance
“…However, it must be kept in mind that there may be individual variations due to individual differences in kinetics, and viral load may increase after an initial decline, and in some cases, it may take as long as a year or more before it reaches stably low levels. Finally, even when this level is reached, the blood of a healthy carrier contains 1-50 copies of EBV DNA per million white blood cells, whereas EBV-DNA is almost always undetectable in plasma or serum [82,85,[93][94][95][96] . The presence of plasma/serum EBV-DNA is therefore considered a sign of primary infection [13] or reactivation, and the viral load correlates with disease severity [85,88,92] .…”
Section: Molecular Biologymentioning
confidence: 99%
See 3 more Smart Citations
“…However, it must be kept in mind that there may be individual variations due to individual differences in kinetics, and viral load may increase after an initial decline, and in some cases, it may take as long as a year or more before it reaches stably low levels. Finally, even when this level is reached, the blood of a healthy carrier contains 1-50 copies of EBV DNA per million white blood cells, whereas EBV-DNA is almost always undetectable in plasma or serum [82,85,[93][94][95][96] . The presence of plasma/serum EBV-DNA is therefore considered a sign of primary infection [13] or reactivation, and the viral load correlates with disease severity [85,88,92] .…”
Section: Molecular Biologymentioning
confidence: 99%
“…Patients with latent infection have an almost constant number of circulating infected B cells in peripheral blood and, in the case of reactivation, these differentiate into plasma cells, leading to the start of the replicative cycle and increased EBV DNA levels in PBMCs and serum/plasma. It has been reported that a search for EBV DNA in PBMCs and serum/plasma is important for an immediate diagnosis of reactivation but, although this is true in the patients who are followed up over time in order to detect any changes in viral load, the finding of EBV DNA in a single sample should not necessarily be seen as a sign of reactivation [95] . Consequently, as EBV DNA is present in cases of reactivation or primary infection, it is unlikely that testing one sample will be able to distinguish the two situations [75,95] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sonuç olarak; EBV DNA hem re-aktivasyon hem primer enfeksiyonda kanda pozitif bulunmakla birlikte bu ikisinin ayrımı tek bir örnekten çalışılan test ile mümkün değildir (12). …”
Section: Introductionunclassified